2007
DOI: 10.1063/1.2763981
|View full text |Cite
|
Sign up to set email alerts
|

Optimal roughness for minimal adhesion

Abstract: Surface roughness has a significant effect on adhesion. We used a singleasperity model to describe a smooth tip in contact with a rough surface and predicted that an optimal size of asperity will yield a minimum of adhesion. Experimentally, adhesive forces on silicon wafers with varying roughness were measured using AFM cantilevers with varying tip radii. It was found that minima do exist, and for all tip radii, the adhesion falls significantly for roughness greater than 1-2 nm and drops at higher roughness fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
38
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 14 publications
7
38
0
Order By: Relevance
“…The adhesion, however, decreases with increasing surface roughness. The latter agrees well with results reported by Liu et al [20].…”
Section: Characterization Of Particle Probes and Si Surfacessupporting
confidence: 83%
“…The adhesion, however, decreases with increasing surface roughness. The latter agrees well with results reported by Liu et al [20].…”
Section: Characterization Of Particle Probes and Si Surfacessupporting
confidence: 83%
“…In the fi rst and second categories, computational or purely theoretical models of contact mechanics are proposed or used, and thus an input value is needed for range of adhesion. As shown in Table 1 , the majority of these studies [ 4,27,31,34,44,45,[48][49][50] estimate the range of adhesion as equal to the interatomic spacing of atoms in the contacting material. While it seems a reasonable ballpark estimate, there is little direct justifi cation provided for this claim.…”
Section: Comparing Range Of Adhesion To Previously Proposed Valuesmentioning
confidence: 99%
“…This quantity is the correct one for use in continuum contact models [4][5][6]8,27,28 ] as well as in roughness models. [ 26,29,30 ] The investigations in this second category have employed the atomic force microscope (AFM), [ 8,12,[31][32][33][34] the related interfacial force microscope (IFM), [ 35 ] and the surface forces apparatus (SFA) [ 36,37 ] to conduct adhesion tests with high-force resolution using a single-asperity contact, typically on the nanometer length scale. Since these are not fl at surfaces, a value for work of adhesion requires using a contact mechanics model to fi t the data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the adhesion force between two surfaces in ambient atmosphere is reduced by two orders of magnitude when the combined surface roughness increases from 1 nm to 10 nm for several different counter-surfaces on gold. 13,29,30 The combined surface roughness of the matrix region of the piezocomposite and wafer is almost 6 nm, which already yields relatively low adhesion forces between silicon and gold. 13 After actuation, the wafer rests solely on the protruding PZT fibers.…”
mentioning
confidence: 99%